Translation and validation of the Chinese version of the Self-awareness Scale for Nurses - Chen, Qing; Liang, Chunguang; Lu, Jing; Jiang, Zhaoquan (Frontiers in Public Health, 2024)
Background: Levels of self-awareness may affect the decision-making ability of clinical nurses and may also be related to mental health. Therefore, it is crucial to develop tools to identify nurses' level of self-awareness. The purpose of this study was to investigate the reliability and validity of a short scale among Chinese nurses and to explore the factors associated with nurses' selfawareness.Methods: A total of 957 participants were recruited, 549 participants were used for reliability tests and 408 subjects were used for impact factor studies. They completed the General Information Questionnaire, the Self-Awareness Scale for Nurses, and the Psychological Distress Scale.Exploratory factor analysis, validation factor analysis, Cronbach's alpha, and retest reliability were used to investigate the psychometric properties of the Self-Awareness Scale for Nurses Multiple regression analyses were used in this study to investigate the relationship between nurses' selfawareness and the independent variables.A 4-factor model of the Chinese version of the Self-Awareness Scale for Nurses was validated. The overall Cronbach's alpha value for the Chinese version of the Self-Awareness Scale for Nurses was 0.873. Cronbach's alpha values for each subscale ranged from 0.808 to 0.979.Significant predictors of each dimension of the Self-awareness and the total score of the scale were age and work experience.The Chinese version of the Self-Awareness Scale for Nurses is a valid and reliable scale.